Estimating the impact of agricultural cooperatives in Senegal: Propensity score matching and endogenous switching regression analysis - K. Christophe Adjin; Anatole Goundan; Christian H. C. A. Henning; Saer Sarr (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
The recent renaissance of the Senegalese cooperative movement coupled with the revival of the agricultural sector motivated this study, which mainly aims to analyse the impact of farmer-based organization membership on household land productivity and net income. We combined the Propensity Score Matching (PSM) method with an Endogenous Switching Regression (ESR) model to derive treatment effects of membership in these farmer organizations using national household-level survey data. Results exhibit consistency across estimations techniques. Estimates of both ESR and PSM models showed that membership in farmer organizations affects positively and significantly the household land productivity and net income. Moreover, findings show that membership has a heterogeneous impact. Households with the lowest probability to be members of farmer organizations have the highest impact. The effect of membership depends also on the specific type of organization.
urn:nbn:de:gbv:8:3-2021-00299-3
Keywords: Q13; D04; Q15; Q12; 330; Farmer organizations; impact evaluation; land productivity; household income; Senegal